Pengaruh Persaingan, Pemberian Jasa Lain, dan Sifat Machiavellian Pada Independensi Auditor - Paramitha Nida, Desak Ruric Pradnya (E-Jurnal Akuntansi; Vol 7 No 3 (2014), 2014)
A public accountant should have an independent attitude in an opinion on the financial statements of a company to avoid errors in the interpretation of the financial statements. This study aimed to determine the effect of competition among public accounting firms, providing services in addition to audit, and the Machiavellian nature of the auditor independence. Location of the study was the registered public accounting firm on the directory Indonesian Institute of Certified Public Accountants Bali region. Sample size was 73 people. The sampling method used was purposive sampling. Data were collected by distributing questionnaires and then analyzed with multiple linear regression. Results from this study is competition among public accounting firms showed a positive effect on auditor independence. While the provision of services other than audit and Machiavellian nature negatively affect auditor independence.
Keywords: Independensi: Persaingan antar Kantor Akuntan Publik: Pemberian Jasa selain Audit: Sifat Machiavellian